The self in neuroscience and psychiatry - Kircher, Tilo 1965-; David, Anthony S. (Cambridge University Press, 2003)
In recent years the clinical and cognitive sciences and neuroscience have contributed important insights to understanding the self. The neuroscientific study of the self and self-consciousness is in its infancy in terms of established models, available data and even vocabulary. However, there are neuropsychiatric conditions, such as schizophrenia, in which the self becomes disordered and this aspect can be studied against healthy controls through experiment, building cognitive models of how the mind works, and imaging brain states. In this 2003 book, the first to address the scientific contribution to an understanding of the self, an eminent, international team focuses on current models of self-consciousness from the neurosciences and psychiatry. These are set against introductory essays describing the philosophical, historical and psychological approaches, making this a uniquely inclusive overview. It will appeal to a wide audience of scientists, clinicians and scholars concerned with the phenomenology and psychopathology of the self